2017
DOI: 10.4067/s0034-98872017000200003
|View full text |Cite
|
Sign up to set email alerts
|

Factores asociados a fragilidad en pacientes hospitalizados con insuficiencia cardiaca descompensada

Abstract: (OR 1.07; previous hospitalizations (OR 2.56;) and number of medications (OR 4.46;. Conclusions: The prevalence of frailty in patients admitted to the hospital for decompensated heart failure is high. Age, quality of life, hospitalizations and polypharmacy were factors associated with frailty in this group of participants. (Rev Med Chile 2017; 145: 164-171)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
(30 reference statements)
0
2
0
1
Order By: Relevance
“…En contraste, el estudio de Díaz-Toro et al . 23 , realizado en Chile, cuyo objetivo fue estimar la prevalencia de fragilidad y evaluar los factores que pudiesen estar asociados en pacientes con FC descompensada, encontró que la edad avanzada (73,8 ± 8,0 vs 68,2 ± 7,1; p < 0,003) la polifarmacia, hospitalizaciones previas y la calidad de vida, son factores que presentaron asociación con fragilidad.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En contraste, el estudio de Díaz-Toro et al . 23 , realizado en Chile, cuyo objetivo fue estimar la prevalencia de fragilidad y evaluar los factores que pudiesen estar asociados en pacientes con FC descompensada, encontró que la edad avanzada (73,8 ± 8,0 vs 68,2 ± 7,1; p < 0,003) la polifarmacia, hospitalizaciones previas y la calidad de vida, son factores que presentaron asociación con fragilidad.…”
Section: Discussionunclassified
“…La relación significativa entre fragilidad y edad discrepa del estudio de Denfel et al, donde no se encontró relaciones significativas entre edad o la clase funcional y la prevalencia de fragilidad (17) , debido a que existe una alta prevalencia de fragilidad en pacientes jóvenes con FC y sugieren que deberíamos considerarla en todo paciente con este diagnóstico, este hallazgo se debe, probablemente, a la interacción de múltiples factores relacionados con la edad y la FC, incluidos la desregulación neurohormonal, la inflamación, la disfunción del musculoesquelético; el subtipo y la gravedad de la FC desde el punto de vista de la desregulación hemodinámica y las comorbilidades que alimentan la enfermedad. En contraste, el estudio de Díaz-Toro et al (23) , realizado en Chile, cuyo objetivo fue estimar la prevalencia de fragilidad y evaluar los factores que pudiesen estar asociados en pacientes con FC descompensada, encontró que la edad avanzada (73,8 ± 8,0 vs 68,2 ± 7,1; p < 0,003) la polifarmacia, hospitalizaciones previas y la calidad de vida, son factores que presentaron asociación con fragilidad.…”
Section: Discussionunclassified
“…In their 2018 study, Uchmanowicz et al [19] also proposed that frailty symptoms are highly prevalent among elderly HF patients, and the severity of frailty is directly associated with higher readmission rates. In the years 2016-2017, Vidán et al (2016) [20] and Díaz-Toro et al (2017) [21] independently reported frailty occurrence rates of 76% and 50.6% respectively in elderly HF patients, suggesting that the incidence of frailty in this population is relatively high. The relevant articles published between 2018 and 2021 also demonstrated that frailty was very common in patients with senile HF [22,23].…”
Section: Relationship Between Senile Hf and Frailtymentioning
confidence: 97%
“…The guidelines report that frailty, regardless of age, is a multidimensional condition that predisposes patients with heart failure to stress factors and has a poor prognosis [ 76 ]. It was found that frailty was high in hospitalized patients with decompensated heart failure, and frailty was associated with age, quality of life, hospitalization, and polypharmacy in these patients [ 77 ]. Acute and chronic heart failure diagnosis and treatment guidelines emphasize that frailty should be considered as a part of the evaluation and in the treatment of heart failure patients [ 78 ].…”
Section: Predictive and Preventive Strategiesmentioning
confidence: 99%